Genomic epidemiological analysis of mcr-1-harboring Escherichia coli collected from livestock settings in Vietnam - Nguyen, Phuong Thi Lan; Ngo, Thi Hong Hanh; Tran, Thi Mai Hung; Vu, Thi Ngoc Bich; Le, Viet Thanh; Tran, Hai Anh; Pham, Duy Thai; Nguyen, Ha Thanh; Tran, Dieu Linh; Nguyen, Thi Phuong Lien; Nguyen, Thi Thi Tho; Tran, Nhu Duong; et al. (Frontiers in Veterinary Science, 2022)
Livestock has been implicated as a reservoir for antimicrobial resistance (AMR) genes that can spread to humans when antimicrobials are used in animals for food production to treat clinical diseases and prevent and control common disease events. In Vietnam, mcr-1-harboring Escherichia coli (MCRPEC) strains have been isolated from humans, animals (chickens, pigs, and dogs) feces, flies, foods, and the environment (rainwater, well water, and irrigation water) in communities and from clinical specimens in hospitals. The relationship between levels of AMR in livestock and its occurrence in humans is complex and is driven by many factors. We conducted whole genome sequencing of MCRPEC to analyze the molecular epidemiological characteristics, history, and relatedness of 50 isolates obtained in 2019 from different reservoirs in farms and markets in Ha Nam province, Vietnam. 34 sequence types (STs) with 3 new STs were identified in multilocus sequence typing analysis: ST12945 and ST12946 from chicken feces, and ST12947 from flies. The AMR phenotypes of 50 MCRPEC isolates were as follows: ampicillin (100%, 50/50), cefotaxime (10%, 5/50), gentamicin (60%, 30/50), amikacin (8%, 4/50), meropenem (6%, 3/50), ceftazidime (18%, 9/50), colistin (24%, 12/50) and ciprofloxacin (80%, 40/50). All 50 MCRPEC isolates were identified as MDR. 100% (50/50) isolates carried AMR genes, ranging from 5 to 22 genes. The most prevalent plasmid replicon types carrying mcr-1 were IncP-1 (17/37, 45.9%), IncX4 (7/37, 18.9%), and IncHI2/IncHI2A (6/37, 16.2%). These data suggest that the epidemiology of the mcr-1 gene is mostly determined by plasmid spreading instead of clonal dissemination of MCRPE strains. The co-occurrence of several STs such as ST10, ST48, ST155, ST206, ST2705 in various sample types, joined to the higher prevalence of a few types of Inc plasmids, confirms the dissemination of the mcr-1 carrying plasmids in E. coli clones established in livestock. 5 over 8 STs identified in flies (ST206, ST2705, ST155, ST10, and ST48) suggested the fly contribution in the transmission of AMR bacteria in environments. These popular STs also occur in human samples and 100% of the human samples were positive for the mcr-1 gene.